College-Going Benefits of High School Sports Participation: Race and Gender Differences Over Three Decades. (May 2015) - Shifrer, Dara; Pearson, Jennifer; Muller, Chandra; Wilkinson, Lindsey
The long touted athlete advantage in college enrollment has been tempered by assertions that this advantage is actually due to characteristics that precede participation. Moreover, it remains unclear whether the benefits of sports extend into contemporary times and apply equally to female and racial minority athletes. This study uses three nationally representative longitudinal data sets of students who were 10th graders in 1980, 1990, and 2002. We find that high school sports participation was positively associated with college enrollment, even with the utilization of propensity score modeling, for White boys and girls, Black boys, and Latino boys and girls during the 1980s, 1990s, and 2000s. The most important gender and race differences include Black female athletes' college-going disadvantage in the 1980s and 1990s, and girls' persistently lower rates of high school sports participation than boys'.